A Potent Mimetic of the Siglec‐8 Ligand 6'‐Sulfo‐Sialyl Lewisx. (4th September 2020) - Kroezen, Blijke S.; Conti, Gabriele; Girardi, Benedetta; Cramer, Jonathan; Jiang, Xiaohua; Rabbani, Said; Müller, Jennifer; Kokot, Maja; Luisoni, Enrico; Ricklin, Daniel; Schwardt, Oliver; Ernst, Beat
Abstract : The Front Cover shows the interaction of the natural ligand 6′‐sulfo‐sialyl Lewis x and a glycomimetic thereof with Siglec‐8, a cell‐surface receptor considered to be a promising target for the treatment of eosinophil‐ and mast‐cell‐associated diseases such as asthma. Using a combination of pharmacophore analysis, NMR structural information, and chemical modification of the initial hit identified by glycan array screening, Ernst and co‐workers were able to generate a high‐affinity glycomimetic. The elucidation of the structure—activity relationship, accompanied by the analysis of binding thermodynamics and kinetics, sheds light on the underlying binding mechanisms. These results exhibit an important contribution to the further development of the therapeutic potential of Siglec‐8 antagonists. (Cover graphics by Gabriele Conti, Department of Pharmaceutical Sciences, University of Basel.) More information can be found in the Full Paper by Beat Ernst et al.